Advanced Analytical and Empirical Control Strategies for Active Magnetic Bearing Systems - Debarghya Dutta; Pabitra Kumar Biswas; Suraj Gupta; Sukanta Debnath; Ameni Boumaiza; Furkan Ahmad (IEEE Access)
Active Magnetic Bearings (AMB) systems are well-suited for high-speed applications and demonstrate compatibility with clean environments, such as renewable energy sectors, and challenging conditions like extreme pressures, temperatures, and harsh environments. This paper provides an in-depth assessment of the control of AMB, which are electromagnetic bearings powered by power electronic components. It highlights the advantages and disadvantages of various control techniques for AMB. However, controlling AMB presents difficulties due to their nonlinear and inherently unstable nature. The work focuses on emphasizing advanced control strategies using Fourier and empirical data-driven engineering approaches, which have significantly expanded the potential applications of AMB across various industries. The article also highlights potential directions in research, emphasizes numerical modeling for AMB using Maxwell’s principle, and presents sophisticated control schemes to comprehend dynamic circumstances.